Analysis Of Fundamental Factors That Affect The Stock Price Of Manufacturing Companies - Rantung, Danny Ivan; Ananto, Niel; Oroh, Nouke Sysca; Koapaha, Hartiny Pop (SEIKO : Journal of Management & Business, 2023)
This study aims to analyze the fundamental factors that affect stock prices in manufacturing companies. There are several fundamental factors used in this study, namely financial ratios consisting of Return on Asset (ROA), Debt to Equity Ratio (DER), Book Value Per Share (BVS). The sampling method used is purposive sampling method. From a population of 133 manufacturing companies listed on the Indonesia Stock Exchange, 36 companies were taken. Hypothesis testing is done using multiple linear regression analysis with panel data, the initial stage is to first conduct a classical assumption test which includes data normality test, multicolonierity, heteroscedasticity and model linearity test. The results of this study indicate that ROA, DER, BVS simultaneously have a significant effect on stock prices. The results of the partial analysis of the fundamental factors Return on Asset (ROA), Debt to Equity Ratio (DER), and Book Value Per Share (BVS) have a positive influence on the stock price of Manufacturing companies on the IDX in 2017-2022. Keyword: Fundamental factors